Environmental Change And It’s Affect - Hossain, Kaizar; Rao, A. Rama (European Journal of Sustainable Development, 2014)
Modern economic development sometimes disrupts nature’s delicate balance. The extent of environmental pollution caused by humans is already so great that some scientist question whether the Earth can continue to support life unless immediate corrective action is taken. If left undisturbed, natural environmental systems tend to achieve balance or stability among the various species of plants and animals. Much of the world’s air, water and land are now partially poisoned by chemical wastes. Some places have become inhabitable. These pollution exposes people all around the globe to new risks from disease. As a result of these developments, governments have passed laws to limit or reverse the threat of environmental pollution. The 19th century, industrial revolution placed greater pressures on the environment. Although industrial development through the control of nature and development of new products improved the standard of living of humans, this was at a great environmental cost. Keywords: Environment, pollution, health, ground water, indicators.